Website Development for Publication and Marketing of ITS-Assisted Halal Product MSME - Nur Aini Rakhmawati; Rarasmaya Indraswari; Eko Setiyo Budi Purnomo; Nadhif Ikbar Wibowo (Universitas Serang Raya, 2022)
The high and increasing number of MSMEs and the importance of socialization and guidance related to halal product policies is one of the factors for the establishment of the Center for Halal Studies (PKH) of Institut Teknologi Sepuluh Nopember (ITS). PKH ITS aims to assist MSMEs in obtaining halal certification and marketing their products. In this community service activity, it is proposed to develop the ITS PKH website (http://halal.its.ac.id/) for of publication and marketing of ITS-assisted MSME’s halal products. The stages in this community service activity include preparation, implementation, documentation, and reporting. The ITS PKH website that we developed contains a complete profile of ITS assisted MSMEs equipped with a QRCode. This unique QRCode leads to the MSME profile page on the ITS PKH website and has been utilized by ITS-assisted MSMEs by being pasted on the website/social media/product packaging of each MSME. This website also has a “Ask Halal” feature to help people search and check halal products. Currently, there are 126 MSMEs spread throughout Indonesia who use the ITS PKH website that we developed. With the features provided by the ITS Halal Study Center website, it is hoped that MSMEs will find it easier to market their products because users find it easy to get and find information related to MSME products.